Major Event-led Strategy for Urban Development and Revitalization - Klinmalai, Siwaporn; Kaewlai, Peeradorn (Journal of Architectural/Planning Research and Studies (JARS), 2023)
Organizing major events is one of the key driving mechanisms for increasing the competitiveness of destination cities, especially for the event host city. In addition to major events, community festivals and local celebrations also play an important role in increasing opportunities for creating lasting heritage because they reflect the unique city culture and their preservation of historical traditions become a cultural property. The readiness of the city also helps support a major event format that is appropriate for the context of the city and its identity. This study examined the readiness of a city through the lens of 6 key factors, i.e., geography, history, culture, tourist attractions or event venues, facilities, and transportation system of the city. In addition, the study assessed event potential for a city using criteria that included: having international content; potential to attract a large number of participants and international media; potential to generate economic benefits for the city; community participation activities; potential of the organizer and the event area; and ability to create a positive event experience. The proposals for the major events are divided into 2 types: local events that have potential to be upgraded to major events; and international major events that can be engaged to organize in the area according to the types of event: sports events, entertainment events, creative and lifestyle events, and art and cultural events. The result of the study revealed the criteria for assessing potential areas for hosting major events within the context of the city characteristics and capabilities. In addition, the contribution of this study provides guidance to a city that would like to be the host of a major event and organize the event, using the city’s assets.